Fiscal Sustainability of the German Laender - Time Series Evidence - Heiko T. Burret; Lars P. Feld; Ekkehard A. Köhler (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this paper we analyze the sustainability of public finances in the states (Laender) of the Federal Republic of Germany using an unprecedentedly comprehensive fiscal dataset for the time period from 1950 to 2011 for West German Laender and 1991 to 2011 for East German Laender, respectively. In order to assess the fiscal sustainability of the (Laender) we, first, examine the stationarity characteristics of public debt, revenues and expenditures. Second, we explore the long]run relation between expenditures and revenues in a cointegration analysis within each Land. The results provide evidence against strict fiscal sustainability in most of the 16 German Laender. A notable exception to this finding is Bavaria.
Keywords: H62; H77; H72; 330; fiscal sustainability; federalism; unit root; cointegration; public debt